1994
DOI: 10.1577/1548-8659(1994)123<0223:amfgsp>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Microassay for Gill Sodium, Potassium-Activated ATPase in Juvenile Pacific Salmonids

Abstract: A microassay well‐plate method is described for determining Na+,K+‐ATPase activities of small gill sections from juvenile Pacific salmon Oncorhynchus spp. The method differs from the established macromethod by detecting inorganic phosphate in nanomole rather than micromole concentrations. This permits the use of much smaller tissue samples, which makes it possible to release fish after sampling. Use of sonication during enzyme extraction and elimination of the need to deproteinize samples before ATPase analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 13 publications
1
41
0
Order By: Relevance
“…During sampling, the left gill arches from each fish were removed, placed in foil and frozen in liquid nitrogen. The gill samples were stored at −80°C and later analyzed to determine Na/K-ATPase enzyme activity [28], [29]. Livers were removed, weighed, and with whole body weights used to calculate the hepatosomatic index (HSI, liver weight/whole body weight ×100).…”
Section: Methodsmentioning
confidence: 99%
“…During sampling, the left gill arches from each fish were removed, placed in foil and frozen in liquid nitrogen. The gill samples were stored at −80°C and later analyzed to determine Na/K-ATPase enzyme activity [28], [29]. Livers were removed, weighed, and with whole body weights used to calculate the hepatosomatic index (HSI, liver weight/whole body weight ×100).…”
Section: Methodsmentioning
confidence: 99%
“…Gill samples were taken from hatchery and wild smolts of the same batches as the tagged fish. A gill biopsy (four to five tips of filaments) was taken from the first gill arch of 10 hatchery and 10 wild smolts and frozen in SEI buffer (300 mm sucrose, 20 mm Na 2 EDTA, 50 mm imidazole, pH 7.3), using the gill biopsy method described by Schrock et al (1994). Gill samples were stored in a −80 • C freezer until Na + ,K + -ATPase activity was analysed (Schrock et al, 1994).…”
Section: Smolt Gill Na + K + -Atpase Activity and Body Compositionmentioning
confidence: 99%
“…Gill and kidney Na + /K + ATPase activity was assayed according to the method described by Schrock et al (1994) with the enzyme activity shown as lmolÁPiÁmg À1 proteinÁh À1 .…”
Section: Measurement Of Gill and Kidney Na + /K + Atpasementioning
confidence: 99%